Modern management : diversity, quality, ethics and the global environment - Certo, Samuel C. (Pearson Educación, 2001)
Requerimientos del sistema: PC Pentium, PC multimedia, Microsoft Windows 95, 98 (32MB RAM) o NT (64MB RAM), 4X CD Rom, SVGA, Microsoft Internet explorer 4.0, QuickTime 3.0x for Windows